Proteome-wide analysis of HIV-specific naive and memory CD4(+) T cells in unexposed blood donors. - Campion, S; Brodie, T; Fischer, W; Korber, B; Rossetti, A; Goonetilleke, N; Mcmichael, A; Sallusto, F (Rockefeller University Press, 2014)
The preexisting HIV-1-specific T cell repertoire must influence both the immunodominance of T cells after infection and immunogenicity of vaccines. We directly compared two methods for measuring the preexisting CD4(+) T cell repertoire in healthy HIV-1-negative volunteers, the HLA-peptide tetramer enrichment and T cell library technique, and show high concordance (r = 0.989). Using the library technique, we examined whether naive, central memory, and/or effector memory CD4(+) T cells specific for overlapping peptides spanning the entire HIV-1 proteome were detectable in 10 HLA diverse, HIV-1-unexposed, seronegative donors. HIV-1-specific cells were detected in all donors at a mean of 55 cells/million naive cells and 38.9 and 34.1 cells/million in central and effector memory subsets. Remarkably, peptide mapping showed most epitopes recognized by naive (88%) and memory (56%) CD4(+) T cells had been previously reported in natural HIV-1 infection. Furthermore, 83% of epitopes identified in preexisting memory subsets shared epitope length matches (8-12 amino acids) with human microbiome proteins, suggestive of a possible cross-reactive mechanism. These results underline the power of a proteome-wide analysis of peptide recognition by human T cells for the identification of dominant antigens and provide a baseline for optimizing HIV-1-specific helper cell responses by vaccination.